Negative Representation of Assad’s Regime in CNN Online Articles - Gina Nanda Utama; Rosaria Mita Amalia (IAIN MADURA, 2019)
This research article discusses the use of chemical weapons in Syria. This study discusses the representation of Assad’s regime in two CNN articles since there is an assumption that Assad’s regime and its alliances are the responsible ones for the chemical weapon issue in Syria. The data is analyzed through Critical Discourse Analysis by Van Dijk as the grand theory so that it is examined by using macro and micro level analysis. This study shows that these articles present the negative representation of Assad’s regime. It can be seen from the negative lexical choices which are used by the writers to describe Assad’s regime and it also can be seen from the writers attempts to present the US’s arguments by trying to legitimize it by frequently using verbal reaction in schematic analysis and the writers of the articles also struggle to hide another version of truth which stated that the responsible one for the use of chemical weapon in Syria is the rebels groups